2016
DOI: 10.1108/jpcc-07-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Opening the black box: knowledge creation in data teams

Abstract: Purpose -In this study, Nonaka and Takeuchi's socialization, externalization, combination and internalization (SECI) model of knowledge creation is used to gain insight into the process of knowledge creation in data teams. These teams are composed of school leaders and teachers, who work together to improve the quality of education. They collaboratively create knowledge related to data use and to an educational problem they are studying. The paper aims to discuss these issues. Design/methodology/approach -A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
(31 reference statements)
2
26
1
Order By: Relevance
“…Apparently, collective ownership is critical for the development of PLCs in schools (Englert and Tarrant 1995). The results of this study build further on recently-published research such as Hubers et al (2016), who concluded that knowledge is created in conversations when members engage in both internalisation and socialisation activities. For example, our results show that socialisation has internal and external impact, referring to both activities within PLCs as well as activities between members of PLCs and colleagues in the schools.…”
Section: General Conclusionsupporting
confidence: 62%
“…Apparently, collective ownership is critical for the development of PLCs in schools (Englert and Tarrant 1995). The results of this study build further on recently-published research such as Hubers et al (2016), who concluded that knowledge is created in conversations when members engage in both internalisation and socialisation activities. For example, our results show that socialisation has internal and external impact, referring to both activities within PLCs as well as activities between members of PLCs and colleagues in the schools.…”
Section: General Conclusionsupporting
confidence: 62%
“…This marks the importance of converting explicit into tacit knowledge which drives business activities and increases knowledge assets in Thai banks. This finding is in line with another research, indicating that the more engagement in socialization and internalization, the deeper knowledge that employees gain in the educational context [42]. In the opposite way, internalization does not affect to organizational performance in social perspective.…”
Section: Results and Conclusionsupporting
confidence: 92%
“…The benefits of teachers collaboratively generating new knowledge about curriculum and teaching in schools or teams are increasingly recognized (Cober, Tan, Slotta, So, & Könings, 2015;Cochran-Smith & Lytle, 1993, 2009Hubers, Poortman, Schildkamp, Pieters, & Handelzalts, 2016;Pareja Roblin, Ormel, McKenney, Voogt, & Pieters, 2014). Effects of teachers' collaborative design on curriculum change have been reported by several scholars (Coburn et al, 2012;Penuel, McWilliams, et al, 2009;Penuel, Sun, Frank, & Gallagher, 2012).…”
Section: Teacher Learning In Curriculum Design Teams: Effectsmentioning
confidence: 99%